2013
DOI: 10.4166/kjg.2013.61.4.219
|View full text |Cite
|
Sign up to set email alerts
|

Septic Pylephlebitis as a Rare Complication of Crohn's Disease

Abstract: Thrombophlebitis of the portal venous system (PVS) with superimposed bacterial infection (septic pylephlebitis) is an extremely rare complication of Crohn's disease (CD), and therefore diagnosis of septic pylephlebitis is difficult without high clinical suspicion. A 16-year old male patient who was diagnosed with CD 3 months earlier was admitted with recurrent fever and abdominal pain. CD activity had been well controlled with conventional medical treatment during a follow-up period. Abdominal contrast-enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
(6 reference statements)
1
4
0
Order By: Relevance
“…The SMV is more commonly thrombosed, and studies suggest that MVTs are found within the same territory in which IBD is located. 9 Our case follows a similar presentation. The prevalence of MVT remains unknown within the IBD population; however, the risk seems to be increased and is speculated to be 8 times higher during a flare.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The SMV is more commonly thrombosed, and studies suggest that MVTs are found within the same territory in which IBD is located. 9 Our case follows a similar presentation. The prevalence of MVT remains unknown within the IBD population; however, the risk seems to be increased and is speculated to be 8 times higher during a flare.…”
Section: Discussionsupporting
confidence: 72%
“…Bowel wall inflammation and localized venous engorgement from MVT could be correlating factors. 9 Pylephlebitis may ensue after bacteria translocate from the site of bowel damage or infection into small veins, draining this area and then become thrombosed. This process extends to involve the portal vein and/or mesenteric veins.…”
Section: Discussionmentioning
confidence: 99%
“…Articles published in languages other than English; cases where clinical, microbiological, or radiological studies did not support the diagnosis; case reports not providing an adequate amount of information, as well as those reporting non-human subjects were excluded from the analyses. The final number of articles included was 101, which resulted in total number of 103 patients [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ,…”
Section: Methodsmentioning
confidence: 99%
“…It is usually secondary to the development of intra-abdominal infective foci typically complicating diverticular disease, appendicitis and necrotizing pancreatitis [2] . This critical clinical condition can arise in inflammatory bowel diseases too [2] , [3] , [4] , [5] , [6] , [7] , [8] . However, in Crohn’s disease it is extremely rare.…”
Section: Discussionmentioning
confidence: 99%
“…Pylephlebitis was described as a Crohn’s disease complication in 1946 by Taylor [3] and, to the best of our knowledge, only other 8 cases have been reported so far [2] , [4] , [5] , [6] , [7] , [8] . Furthermore, only in three of them the superior mesenteric vein was described to be primarily involved.…”
Section: Introductionmentioning
confidence: 95%